MANAGING LAND RE/DIS-POSSESSION FROM BELOW: HISTORY OF BIOPOLITICS COUNTERMOVEMENT IN TWO JAVANESE RURAL COMMUNITIES - Shohibuddin, Mohamad (History Department, Semarang State University and Historian Society of Indonesia, 2014)
The long debate on whether rural community in Java is more characterised as egalitarian or differentiated one has underrated the agency of the local people. This paper tries to propose the agency of local people through a comparative account upon history of two communities, namely Ngandagan in Central Java and Wangunwati in West Java. Mobilizing the collective action toward land struggle, both communities involved in a broad spectrum of property relations reform which ranged from struggles over material things, revenue, to political power. As those struggles reflect interventions for â€œmaking liveâ€ and â€œnot letting dieâ€ of the local population, this paper argues that both communities engaged in biopolitics countermovement directed to market and political forces threatening their means of livelihoods and even their life. However, while two communities succeeded in transforming inter-groups property relations within community, their political future would eventually necessitate the broader transformation of property relations between the state and the society.Keywords: history of rural community, agrarian crises, the agency of local people, land struggle, property relations reform, biopolitics, Java, Indonesia.Perdebatan panjang mengenai apakah komunitas pedesaan di Jawa lebih bercorak egalitarian atau terdiferensiasi telah menyebabkan agensi penduduk lokal kurang diperhatikan. Paper ini mencoba mengedepankan agensi komunitas lokal melalui uraian komparatif atas sejarah dua komunitas, yakni Ngandagan di Jawa Tengah dan Wangunwati di Jawa Barat. Memobilisasikan aksi kolektif seputar perjuangan atas tanah, kedua komunitas ini terlibat dalam pembaruan relasi-relasi kepemilikan dalam spektrum yang luas, yang terentang dari perjuangan atas kepemilikan menyangkut benda material, pendapatan, hingga kekuasaan politik. Mengingat perjuangan demikian mencerminkan intervensi untuk â€œmembuat hidupâ€ dan â€œtidak membiarkan matiâ€ atas penduduk lokal, paper ini berargumen bahwa kedua komunitas tersebut menjalankan gerakan perlawanan biopolitics yang ditujukan pada kekuatan pasar dan politik yang mengancam sarana penghidupan dan bahkan jiwa mereka. Namun, sementara keduanya berhasil dalam mentransformasikan relasi-relasi kepemilikan di dalam komunitas, masa depan politik mereka pada akhirnya akan menuntut transformasi lebih luas dalam relasi-relasi kepemilikan antara negara dan masyarakat.Kata kunci: sejarah komunitas pedesaan, krisis agraria, agensi masyarakat lokal, perjuangan atas tanah, pembaruan relasi-relasi kepemilikan, biopolitics, Jawa, Indonesia.Â